Adolescents' Physical Activity in Physical Education, School Recess, and Extra-Curricular Sport by Motivational Profiles. Issue 3 (June 2014) - Mayorga-Vega, Daniel; Viciana, Jesús
The main purpose of this study was to evaluate the differences in adolescents' objective physical activity levels and perceived effort in physical education, school recess, and extra-curricular organized sport by motivational profiles in physical education. A sample of 102 students 11–16 yr. old completed a self-report questionnaire assessing self-determined motivation toward physical education. Subsequently, students' objective physical activity levels (steps/min., METs, and moderate-to-vigorous physical activity) and perceived effort were evaluated for each situation. Cluster analysis identified a two-cluster structure: "Moderate motivation toward physical education profile" and "High motivation toward physical education profile." Adolescents in the second cluster had higher physical activity and perceived effort values than adolescents in the first cluster, except for METs and moderate-to-vigorous physical activity in extra-curricular sport. These results support the importance of physical education teachers who should promote self-determined motivation toward physical education so that students can reach the recommended physical activity levels.